Development of simulation model of HPC system for Super Charm-Tau factory. (November 2019) - Weins, D; Vorobyev, V; Chernykh, I; Logashenko, I
Abstract: The article describes the design of a digital model of an HPC system for processing data from the Super Charm-Tau factory electron-positron collider of the "megascience" class. This model is developed using the AGNES multiagent modeling platform. The model includes intelligent agents that mimic the behavior of the main subsystems of the supercomputer, such as a task scheduler, computing clusters, data storage system, etc. This model allows calculating the parameters of the computing system necessary for processing and storing the results of operation of the Super Charm-Tau factory after its commissioning.